REVIEWS - Newman, Judith H. (Journal of Semitic studies, 2003)
Into the Temple Courts: the Place of the Synagogues in the Second Temple Period (SBL Dissertation Series 169) Donald M.Binder . Scholars Press, Atlanta 1999. Pp. xix + 566. Price: $60.00 hardback. ISBN: 0-88414-008-3.